The revolution will not be downloaded : dissent in the digital age - Brabazon, Tara (Chandos internet series., 2008)
This book attacks the often implicit and damaging assumption that 'everyone' is online and that 'everyone' is using online resources within the specified parameters of employers, government and national laws. This book summons a critical Web Studies, asking not only who is using particular applications, but also how and why. This remedial work is required. The concept and label of 'Web 2.0' is part of a wide-ranging suite of assumptions that offer simple answers to difficult questions. The term captures a desire for online collaboration and the sharing of information, performed most visibly th.